2008
DOI: 10.1111/j.1600-6143.2008.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Cardiac Cirrhosis Following Orthotopic Heart Transplantation

Abstract: Irreversible hepatic cirrhosis greatly increases the risks attending heart transplantation (HT), and is accordingly considered to be an absolute contraindication for HT unless combined heart and liver transplantation can be performed. It is now recognized that hepatic cirrhosis can undergo regression if the source of insult is removed, but no cases of post-HT regression of cirrhosis of cardiac origin have hitherto been reported. Here we report a case of cardiac cirrhosis that underwent complete regression foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
3
23
1
Order By: Relevance
“…Our data add to the existing evidence in the literature that patients with cardiac hepatopathy may, if carefully selected after considering additional clinical and laboratory parameters, be appropriate candidates for cardiac transplantation. 8,11,13,14 Our findings are in agreement with studies that have shown that after successful cardiac transplantation, patients may show improvement of liver disease in terms of both laboratory values and histologic findings. 11,13,14 Our patients all showed marked improvement in liver enzymes and bilirubin levels at 6 months and further improvement at 1 year post-transplant with normal levels observed in most patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data add to the existing evidence in the literature that patients with cardiac hepatopathy may, if carefully selected after considering additional clinical and laboratory parameters, be appropriate candidates for cardiac transplantation. 8,11,13,14 Our findings are in agreement with studies that have shown that after successful cardiac transplantation, patients may show improvement of liver disease in terms of both laboratory values and histologic findings. 11,13,14 Our patients all showed marked improvement in liver enzymes and bilirubin levels at 6 months and further improvement at 1 year post-transplant with normal levels observed in most patients.…”
Section: Discussionsupporting
confidence: 91%
“…8,11,13,14 Our findings are in agreement with studies that have shown that after successful cardiac transplantation, patients may show improvement of liver disease in terms of both laboratory values and histologic findings. 11,13,14 Our patients all showed marked improvement in liver enzymes and bilirubin levels at 6 months and further improvement at 1 year post-transplant with normal levels observed in most patients. One patient (patient #3) showed decreased fibrosis on a follow-up liver biopsy 6 years after heart transplant, providing some evidence that fibrosis in the context of chronic passive congestion may be, to some degree, reversible; however, these findings may also be subject to the limitations of biopsy sampling and the possibility of patchy fibrosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…14 However, there is only one case report supporting the reversibility of congestive hepatic fibrosis after normalization of increased right heart pressure following heart transplantation. 15 The clinical study of Dichtl et al 16 comprising 56 adult patients receiving heart transplantation indicated that many of the elevated liver tests significantly improve within 3 months after heart transplantation. 16 In this setting, congestive hepatic fibrosis score will be useful to assess the reversibility of hepatic fibrosis following cardiac transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort study over 10 years among patients who had received LTx, all cholestatic parameters, transaminases and LDH improved after the procedure. Interestingly, a complete reversal of cardiac cirrhosis 10 years after HTx has even been reported [123,124] . A careful assessment of liver function and detection of liver cirrhosis is required in all candidates for HTx.…”
Section: Heart Transplantationmentioning
confidence: 99%